High-salt-resistant metal antirust agent and preparation method thereof

By using raw materials such as triethanolamine oleic acid salt in metal anti-rust agents, and through the synergistic effect of nanomodifiers and chitosan regulation liquid, the problem of poor rust anti-rust performance in the existing technology in high salt and humid and heat environments is solved, and the coordination improvement of adhesion and rust anti-rust performance and improvement of performance stability is achieved.

CN119571329APending Publication Date: 2025-03-07GUANGZHOU CAMAROL LUBRICANTS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411555465.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The existing metal anti-rust agent has poor anti-rust performance in high salt and humid and heat environments, and it is difficult to coordinately improve adhesion and anti-rust performance.

Method used

High-salt-resistant metal anti-rust agents are prepared by using raw materials such as triethanolamine oleic acid salt, nanomodifiers, chitosan regulation solution, dimethyl silicone oil, sodium tripolyphosphate, triethanolamine and silane coupling agent KH560, etc. The nanomodifier is improved through heat treatment, modification liquid treatment and ball milling to enhance anti-rust protection and adhesion; the chitosan regulation liquid further enhances performance stability through coordination with sheet-like graphene.

Benefits of technology

It significantly improves the anti-rust performance of metal anti-rust agents in high salt and humid and heat environments, coordinates and improves adhesion and anti-rust performance, and improves the efficiency and performance stability of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a high-salt-resistant metal antirust agent which comprises the following raw materials in parts by weight: 30-35 parts of triethanolamine oleate, 5-10 parts of a nano modifier, 4-7 parts of a chitosan regulating solution, 3-5 parts of dimethyl silicone oil, 2-4 parts of sodium tripolyphosphate, 2-4 parts of triethanolamine, 2-3 parts of a silane coupling agent KH560 and 35-40 parts of water. According to the metal antirust agent, triethanolamine oleate, simethicone, sodium tripolyphosphate, triethanolamine and the silane coupling agent KH560 are adopted as matrix raw materials, and the nano modifier and the chitosan adjusting liquid are added to coordinate and cooperate for joint synergism, so that the high-salt and damp-heat antirust performance effects of the product are remarkable, and the adhesive force and the antirust performance of the product are coordinated and improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal rust inhibitors, and in particular to a high-salt resistant metal rust inhibitor and a preparation method thereof. Background Art

[0002] Rust inhibitors refer to temporary anti-corrosion agents used in the transportation process (production, storage and transportation) of metal products. Metal rust inhibitors mainly form a protective film on the metal surface to isolate it from the air, water and other environments, and are supplemented with some metal film-forming agents to reduce the activity of the metal, slow down the rate of metal oxidation and corrosion, and control the oil film by selecting different film-forming agents and dispersants to achieve the effect of rust prevention and metal protection.

[0003] Existing metal rust inhibitors have poor adhesion performance, and also poor high salt, wet heat and rust prevention performance. It is difficult to coordinate and improve the adhesion and rust prevention performance of the product, which limits the use efficiency of the product. Summary of the invention

[0004] In view of the defects of the prior art, the object of the present invention is to provide a high-salt resistant metal rust inhibitor and a preparation method thereof to solve the problems raised in the above background technology.

[0005] The present invention solves the technical problem by adopting the following technical solution: The present invention provides a high-salt resistant metal rust inhibitor, comprising the following raw materials in parts by weight: 30-35 parts of triethanolamine oleate, 5-10 parts of nano modifier, 4-7 parts of chitosan regulating liquid, 3-5 parts of dimethyl silicone oil, 2-4 parts of sodium tripolyphosphate, 2-4 parts of triethanolamine, 2-3 parts of silane coupling agent KH560, and 35-40 parts of water.

[0006] Preferably, the rust inhibitor is the following raw materials in parts by weight: 32.5 parts of triethanolamine oleate, 7.5 parts of nano modifier, 5.5 parts of chitosan regulating liquid, 4 parts of dimethyl silicone oil, 3 parts of sodium tripolyphosphate, 3 parts of triethanolamine, 2.5 parts of silane coupling agent KH560, and 37.5 parts of water.

[0007] Preferably, the preparation method of the nano modifier is: S1: heat-treat the nano-bentonite at 210-230°C for 5-10 min, then cool to 55°C at a rate of 2-4°C / min, and keep warm; Add 2-4 parts of sodium dodecylbenzene sulfonate solution to 4-7 parts of yttrium nitrate solution, and then add 1-2 parts of urea and 1-3 parts of hydroxyapatite to mix well to obtain a modified solution; The heat-insulated nano-bentonite and the modified liquid are stirred and modified in a weight ratio of 2:5. After the modification is completed, the modified nano-bentonite is washed, filtered and dried to obtain the modified nano-bentonite. S2: The modified nano bentonite and the ball milling liquid are subjected to ball milling treatment in a weight ratio of 5:2. After the ball milling is completed, the modified nano bentonite and the ball milling liquid are washed with water and dried to obtain a nano modifier.

[0008] Preferably, the mass fraction of the yttrium nitrate solution is 2-5%; the mass fraction of the sodium dodecylbenzene sulfonate solution is 4-7%.

[0009] Preferably, the rotation speed of the stirring modification treatment is 550-750 r / min, and the modification time is 30-40 min.

[0010] Preferably, the ball milling speed of the ball milling improvement treatment is 1000-1500 r / min, and the ball milling is for 1 hour.

[0011] Preferably, the ball milling liquid comprises the following raw materials in parts by weight: 2-4 parts of nano silica sol, 1-3 parts of lanthanum oxide, 2-5 parts of sodium lignin sulfonate solution, 1-3 parts of silane coupling agent KH550.

[0012] Preferably, the mass fraction of the sodium lignin sulfonate solution is 2-5%.

[0013] Preferably, the preparation method of the chitosan regulating solution is: S11: heat-treating the nano-sheet graphene for 5-10 minutes at a temperature of 125-135° C., and then air-cooling to room temperature after the treatment. S12: The nanosheet graphene cooled to room temperature is immersed in a 5% chitosan solution with a mass fraction of 3-5 times the total amount of the nanosheet graphene, and then sodium citrate with a mass fraction of 2-5% of the total amount of the nanosheet graphene is added and mixed to obtain a chitosan regulating solution.

[0014] The present invention also provides a method for preparing a high-salt resistant metal rust inhibitor, comprising the following steps: adding raw materials into a stirrer in sequence for stirring, the stirring speed being 1000-1500 r / min, the stirring time being 25-35 min, and the stirring being completed to obtain the high-salt resistant metal rust inhibitor of the present invention.

[0015] Compared with the prior art, the present invention has the following beneficial effects: The metal rust inhibitor of the invention adopts triethanolamine oleate, dimethyl silicone oil, sodium tripolyphosphate, triethanolamine and silane coupling agent KH560 as matrix raw materials, and a nano modifier and a chitosan regulating liquid are added to coordinate and cooperate to enhance the synergy, so that the high-salt and wet-heat rust prevention performance of the product is remarkable, and the adhesion and rust prevention performance of the product are coordinated and improved; nano bentonite is used as a lamellar structure to intersperse in the system to enhance the rust prevention protection of the system, and the coordinated synergistic effect of the nano bentonite and the ball milling liquid is optimized by the modified liquid, and the improved nano modifier is used in the system to enhance the adhesion performance and performance stability of the system; and the chitosan regulating liquid adopts flaky graphene to coordinate and further strengthen the performance stability of the system, so that the performance of the product is further improved. DETAILED DESCRIPTION

[0016] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0017] The high-salt resistant metal rust inhibitor of this embodiment includes the following raw materials in parts by weight: 30-35 parts of triethanolamine oleate, 5-10 parts of nano modifier, 4-7 parts of chitosan regulating liquid, 3-5 parts of dimethyl silicone oil, 2-4 parts of sodium tripolyphosphate, 2-4 parts of triethanolamine, 2-3 parts of silane coupling agent KH560, and 35-40 parts of water.

[0018] The rust inhibitor of this embodiment is the following raw materials in parts by weight: 32.5 parts of triethanolamine oleate, 7.5 parts of nano modifier, 5.5 parts of chitosan regulating liquid, 4 parts of dimethyl silicone oil, 3 parts of sodium tripolyphosphate, 3 parts of triethanolamine, 2.5 parts of silane coupling agent KH560, and 37.5 parts of water.

[0019] The preparation method of the nano modifier of this embodiment is: S1: heat-treat the nano-bentonite at 210-230°C for 5-10 min, then cool to 55°C at a rate of 2-4°C / min, and keep warm; Add 2-4 parts of sodium dodecylbenzene sulfonate solution to 4-7 parts of yttrium nitrate solution, and then add 1-2 parts of urea and 1-3 parts of hydroxyapatite to mix well to obtain a modified solution; The heat-insulated nano-bentonite and the modified liquid are stirred and modified in a weight ratio of 2:5. After the modification is completed, the modified nano-bentonite is washed, filtered and dried to obtain the modified nano-bentonite. S2: The modified nano bentonite and the ball milling liquid are subjected to ball milling treatment in a weight ratio of 5:2. After the ball milling is completed, the modified nano bentonite and the ball milling liquid are washed with water and dried to obtain a nano modifier.

[0020] The mass fraction of the yttrium nitrate solution in this embodiment is 2-5%; the mass fraction of the sodium dodecylbenzene sulfonate solution is 4-7%.

[0021] The rotation speed of the stirring modification process in this embodiment is 550-750 r / min, and the modification time is 30-40 min.

[0022] The ball milling speed of the improved ball milling process in this embodiment is 1000-1500 r / min, and the ball milling is performed for 1 hour.

[0023] The ball milling solution of this embodiment includes the following raw materials in parts by weight: 2-4 parts of nano silica sol, 1-3 parts of lanthanum oxide, 2-5 parts of sodium lignin sulfonate solution, 1-3 parts of silane coupling agent KH550.

[0024] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 2-5%.

[0025] The preparation method of the chitosan regulating solution of the present embodiment is: S11: heat-treating the nano-sheet graphene for 5-10 minutes at a temperature of 125-135° C., and then air-cooling to room temperature after the treatment. S12: The nanosheet graphene cooled to room temperature is immersed in a 5% chitosan solution with a mass fraction of 3-5 times the total amount of the nanosheet graphene, and then sodium citrate with a mass fraction of 2-5% of the total amount of the nanosheet graphene is added and mixed to obtain a chitosan regulating solution.

[0026] The preparation method of a high-salt resistant metal rust inhibitor of the present embodiment comprises the following steps: adding raw materials into a mixer in sequence for stirring, the stirring speed is 1000-1500r / min, the stirring time is 25-35min, and the stirring is completed to obtain the high-salt resistant metal rust inhibitor of the present invention.

[0027] Example 1. The high-salt resistant metal rust inhibitor of this embodiment includes the following raw materials in parts by weight: 30 parts of triethanolamine oleate, 5 parts of nano modifier, 4 parts of chitosan regulating liquid, 3 parts of dimethyl silicone oil, 2 parts of sodium tripolyphosphate, 2 parts of triethanolamine, 2 parts of silane coupling agent KH560, and 35 parts of water.

[0028] The preparation method of the nano modifier of this embodiment is: S1: The nano-bentonite was first heat treated at 210°C for 5 min, then the temperature was reduced to 55°C at a rate of 2°C / min and kept warm; Add 2 parts of sodium dodecylbenzene sulfonate solution to 4 parts of yttrium nitrate solution, and then add 1 part of urea and 1 part of hydroxyapatite to mix well to obtain a modified solution; The heat-insulated nano-bentonite and the modified liquid are stirred and modified in a weight ratio of 2:5. After the modification is completed, the modified nano-bentonite is washed, filtered and dried to obtain the modified nano-bentonite. S2: The modified nano bentonite and the ball milling liquid are subjected to ball milling treatment in a weight ratio of 5:2. After the ball milling is completed, the modified nano bentonite and the ball milling liquid are washed with water and dried to obtain a nano modifier.

[0029] The mass fraction of the yttrium nitrate solution in this embodiment is 2%; the mass fraction of the sodium dodecylbenzene sulfonate solution is 4%.

[0030] The rotation speed of the stirring modification process in this embodiment is 550 r / min, and the modification time is 30 min.

[0031] The ball milling speed of the ball milling improvement treatment in this embodiment is 1000r / min, and the ball milling is 1h.

[0032] The ball milling solution of this embodiment includes the following raw materials in parts by weight: 2 parts of nano-silica sol, 1 part of lanthanum oxide, 2 parts of sodium lignin sulfonate solution, and 1 part of silane coupling agent KH550.

[0033] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 2%.

[0034] The preparation method of the chitosan regulating solution of the present embodiment is: S11: heat-treating the nano-sheet graphene for 5 minutes at a temperature of 125° C., and then air-cooling to room temperature after the treatment is completed; S12: The nanosheet graphene cooled to room temperature is immersed in a 5% chitosan solution with a mass fraction of 3 times the total amount of the nanosheet graphene, and then sodium citrate with a mass fraction of 2% of the total amount of the nanosheet graphene is added and mixed to obtain a chitosan regulating solution.

[0035] The preparation method of a high-salt resistant metal rust inhibitor of the present embodiment comprises the following steps: adding raw materials into a mixer in sequence for stirring, the stirring speed is 1000 r / min, the stirring time is 25 min, and the stirring is completed to obtain the high-salt resistant metal rust inhibitor of the present invention.

[0036] Example 2. The high-salt resistant metal rust inhibitor of this embodiment includes the following raw materials in parts by weight: 35 parts of triethanolamine oleate, 10 parts of nano modifier, 7 parts of chitosan regulating liquid, 5 parts of dimethyl silicone oil, 4 parts of sodium tripolyphosphate, 4 parts of triethanolamine, 3 parts of silane coupling agent KH560, and 40 parts of water.

[0037] The preparation method of the nano modifier of this embodiment is: S1: The nano-bentonite was first heat treated at 230°C for 10 min, then the temperature was reduced to 55°C at a rate of 4°C / min and kept warm; 4 parts of sodium dodecylbenzene sulfonate solution are added to 7 parts of yttrium nitrate solution, and then 2 parts of urea and 3 parts of hydroxyapatite are added and mixed to obtain a modified solution; The heat-insulated nano-bentonite and the modified liquid are stirred and modified in a weight ratio of 2:5. After the modification is completed, the modified nano-bentonite is washed, filtered and dried to obtain the modified nano-bentonite. S2: The modified nano bentonite and the ball milling liquid are subjected to ball milling treatment in a weight ratio of 5:2. After the ball milling is completed, the modified nano bentonite and the ball milling liquid are washed with water and dried to obtain a nano modifier.

[0038] The mass fraction of the yttrium nitrate solution in this embodiment is 5%; the mass fraction of the sodium dodecylbenzene sulfonate solution is 7%.

[0039] The rotation speed of the stirring modification process in this embodiment is 750 r / min, and the modification time is 40 min.

[0040] The ball milling speed of the ball milling improvement treatment in this embodiment is 1500r / min, and the ball milling is 1h.

[0041] The ball milling solution of this embodiment includes the following raw materials in parts by weight: 4 parts of nano-silica sol, 3 parts of lanthanum oxide, 5 parts of sodium lignin sulfonate solution, and 3 parts of silane coupling agent KH550.

[0042] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 5%.

[0043] The preparation method of the chitosan regulating solution of the present embodiment is: S11: heat-treating the nano-sheet graphene for 10 minutes at a temperature of 135° C., and then air-cooling to room temperature after the treatment is completed; S12: The nanosheet graphene cooled to room temperature is immersed in a 5% chitosan solution with a mass fraction of 5 times the total amount of the nanosheet graphene, and then sodium citrate with a mass fraction of 5% of the total amount of the nanosheet graphene is added and mixed to obtain a chitosan regulating solution.

[0044] The preparation method of a high-salt resistant metal rust inhibitor of the present embodiment comprises the following steps: adding raw materials into a mixer in sequence for stirring, the stirring speed is 1500r / min, the stirring time is 35min, and the stirring is completed to obtain the high-salt resistant metal rust inhibitor of the present invention.

[0045] Example 3. The high-salt resistant metal rust inhibitor of this embodiment includes the following raw materials in parts by weight: 32.5 parts of triethanolamine oleate, 7.5 parts of nano modifier, 5.5 parts of chitosan regulating liquid, 4 parts of dimethyl silicone oil, 3 parts of sodium tripolyphosphate, 3 parts of triethanolamine, 2.5 parts of silane coupling agent KH560, and 37.5 parts of water.

[0046] The preparation method of the nano modifier of this embodiment is: S1: The nano-bentonite was first heat treated at 220°C for 7.5 min, then the temperature was reduced to 55°C at a rate of 3°C / min and kept warm; Add 3 parts of sodium dodecylbenzene sulfonate solution to 5.5 parts of yttrium nitrate solution, and then add 1.5 parts of urea and 2 parts of hydroxyapatite to mix well to obtain a modified solution; The heat-insulated nano-bentonite and the modified liquid are stirred and modified in a weight ratio of 2:5. After the modification is completed, the modified nano-bentonite is washed, filtered and dried to obtain the modified nano-bentonite. S2: The modified nano bentonite and the ball milling liquid are subjected to ball milling treatment in a weight ratio of 5:2. After the ball milling is completed, the modified nano bentonite and the ball milling liquid are washed with water and dried to obtain a nano modifier.

[0047] The mass fraction of the yttrium nitrate solution in this embodiment is 3.5%; the mass fraction of the sodium dodecylbenzene sulfonate solution is 5.5%.

[0048] The rotation speed of the stirring modification process in this embodiment is 600 r / min, and the modification time is 35 min.

[0049] The ball milling speed of the ball milling improvement treatment in this embodiment is 1250r / min, and the ball milling is 1h.

[0050] The ball milling solution of this embodiment includes the following raw materials in parts by weight: 3 parts of nano silica sol, 2 parts of lanthanum oxide, 3.5 parts of sodium lignin sulfonate solution, and 2 parts of silane coupling agent KH550.

[0051] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 3.5%.

[0052] The preparation method of the chitosan regulating solution of the present embodiment is: S11: heat treating the nano-sheet graphene for 7.5 min at a temperature of 130° C., and then air cooling to room temperature after the treatment is completed; S12: The nanosheet graphene cooled to room temperature is immersed in a 5% chitosan solution with a mass fraction of 4 times the total amount of the nanosheet graphene, and then sodium citrate with a mass fraction of 3.5% of the total amount of the nanosheet graphene is added and mixed to obtain a chitosan regulating solution.

[0053] The preparation method of a high-salt resistant metal rust inhibitor of the present embodiment comprises the following steps: adding raw materials into a mixer in sequence for stirring, the stirring speed is 1250 r / min, the stirring time is 30 min, and the stirring is completed to obtain the high-salt resistant metal rust inhibitor of the present invention.

[0054] Comparative Example 1. The difference from Example 3 is that no nano modifier is added.

[0055] Comparative Example 2. The difference from Example 3 is that no modification liquid treatment is used in the preparation of the nano-modifier.

[0056] Comparative Example 3. The difference from Example 3 is that no urea or hydroxyapatite is added to the modified liquid.

[0057] Comparative Example 4. The difference from Example 3 is that the ball milling liquid treatment is not used in the preparation of the nano-modifier.

[0058] Comparative Example 5. The difference from Example 3 is that no chitosan regulating solution was added.

[0059] The product performance tests of Examples 1-3 and Comparative Examples 1-5 are as follows:

[0060] It can be seen from Comparative Examples 1-5 and Examples 1-3 that the adhesion performance of the product of the present invention to the substrate is remarkable, and the anti-rust stability of the product under high humidity, high heat conditions and high salt spray conditions is remarkable; The performance of the product without adding the nano-modifier and the chitosan regulating liquid of the present invention deteriorates significantly. The synergistic combination of the two and the joint synergy can achieve the most obvious product performance effect. In addition, the nano-modifier is prepared without using the modifying liquid for treatment, without adding urea and hydroxyapatite to the modifying liquid, and without using the ball milling liquid for treatment. The performance of the product has a tendency to deteriorate. The method and raw materials of the present invention are used, and the product performance effect is the most obvious.

[0061] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0062] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A high-salt resistant metal rust inhibitor, characterized in that: It includes the following raw materials in parts by weight: 30-35 parts of triethanolamine oleate, 5-10 parts of nano modifier, 4-7 parts of chitosan regulating liquid, 3-5 parts of dimethyl silicone oil, 2-4 parts of sodium tripolyphosphate, 2-4 parts of triethanolamine, 2-3 parts of silane coupling agent KH560, and 35-40 parts of water.

2. A high salt resistant metal rust inhibitor according to claim 1, characterized in that: The rust inhibitor is the following raw materials in parts by weight: 32.5 parts of triethanolamine oleate, 7.5 parts of nano modifier, 5.5 parts of chitosan regulating liquid, 4 parts of dimethyl silicone oil, 3 parts of sodium tripolyphosphate, 3 parts of triethanolamine, 2.5 parts of silane coupling agent KH560, and 37.5 parts of water.

3. The high-salt resistant metal rust inhibitor according to claim 1, characterized in that: The preparation method of the nano modifier is: S1: heat-treat the nano-bentonite at 210-230°C for 5-10 min, then cool to 55°C at a rate of 2-4°C / min, and keep warm; Add 2-4 parts of sodium dodecylbenzene sulfonate solution to 4-7 parts of yttrium nitrate solution, and then add 1-2 parts of urea and 1-3 parts of hydroxyapatite to mix well to obtain a modified solution; The heat-insulated nano-bentonite and the modified liquid are stirred and modified in a weight ratio of 2:

5. After the modification is completed, the modified nano-bentonite is washed, filtered and dried to obtain the modified nano-bentonite. S2: The modified nano bentonite and the ball milling liquid are subjected to ball milling treatment in a weight ratio of 5:

2. After the ball milling is completed, the modified nano bentonite and the ball milling liquid are washed with water and dried to obtain a nano modifier.

4. A high salt resistant metal rust inhibitor according to claim 3, characterized in that: The mass fraction of the yttrium nitrate solution is 2-5%; the mass fraction of the sodium dodecylbenzene sulfonate solution is 4-7%.

5. The high-salt resistant metal rust inhibitor according to claim 3, characterized in that: The rotation speed of the stirring modification treatment is 550-750r / min, and the modification time is 30-40min.

6. The high-salt resistant metal rust inhibitor according to claim 3, characterized in that: The ball milling speed of the ball milling improvement treatment is 1000-1500r / min, and the ball milling is 1h.

7. The high-salt resistant metal rust inhibitor according to claim 3, characterized in that: The ball milling liquid comprises the following raw materials in parts by weight: 2-4 parts of nano silica sol, 1-3 parts of lanthanum oxide, 2-5 parts of sodium lignin sulfonate solution, 1-3 parts of silane coupling agent KH550.

8. A high salt resistant metal rust inhibitor according to claim 7, characterized in that: The mass fraction of the sodium lignin sulfonate solution is 2-5%.

9. The high-salt resistant metal rust inhibitor according to claim 3, characterized in that: The preparation method of the chitosan regulating solution is: S11: heat-treating the nano-sheet graphene for 5-10 minutes at a temperature of 125-135° C., and then air-cooling to room temperature after the treatment. S12: The nanosheet graphene cooled to room temperature is immersed in a 5% chitosan solution with a mass fraction of 3-5 times the total amount of the nanosheet graphene, and then sodium citrate with a mass fraction of 2-5% of the total amount of the nanosheet graphene is added and mixed to obtain a chitosan regulating solution.

10. A method for preparing a high-salt resistant metal rust inhibitor according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: adding raw materials into a stirrer in sequence for stirring, the stirring speed is 1000-1500 r / min, the stirring time is 25-35 min, and after the stirring is completed, the high-salt-resistant metal rust inhibitor of the invention is obtained.